Analisis Luas Lahan Terdampak Dan Perubahan Pola Permukiman Akibat Abrasi Sungai Di Desa Muara Sampara Periode 2014-2024 - Ahsan, Laode Muhammad Fahrizal; Muhsar, Muhammad; Makmur, Muzammil; Aditya, Muhammad Fathur; Alamsyah, Nur (Sultra Civil Engineering Journal (SCiEJ), 2025)
River abrasion is a natural disaster that causes land erosion due to strong water currents or waves, leading to significant impacts on human settlements and land use. This study analyzes the extent of land loss and changes in settlement patterns caused by river abrasion in Muara Sampara Village, Kapoiala District, Konawe Regency, from 2014 to 2024. Using a Geographic Information System (GIS) approach with high-resolution satellite imagery, overlay analysis was conducted to determine the spatial dynamics of land use and the extent of areas affected by abrasion. The results show that the total land area of the village decreased by 3.23 hectares over ten years, with the highest rate of abrasion occurring between 2016 and 2018. The analysis also indicates a gradual shift in settlement patterns from riverbanks toward safer central areas of the village, reflecting community adaptation to environmental changes. These findings provide crucial spatial information to support local government policies on riverbank management, disaster mitigation, and sustainable land use planning